2002
DOI: 10.1109/tdei.2002.1038664
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric mixtures: electrical properties and modeling

Abstract: A review of current state of understanding of dielectric mixture properties and approaches to use numerical calculations for their modeling are presented. It is shown that interfacial polarization can yield different non-Debye dielectric responses depending on the properties of the constituents, their concentrations and geometrical arrangements. Future challenges on the subject are also discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
161
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(163 citation statements)
references
References 343 publications
2
161
0
Order By: Relevance
“…As discussed previously, at high temperatures close to 300 C, the data for the wet and dried sample are converging to each other indicating the similarities in both responses and confirm that the initial measurement in the first ramp is a dry-bake cycle. The relaxations related to the molecular nature of the material are associated in the dried sample, which indicated three significant processes; (i) a low temperature relaxation attributed to the local (segmental) molecular motion often called as the Johari-Goldstein ( ) relaxation; [26][27][28] (ii) the glass-transition related loss from cooperative ( ) relaxation at mid-temperatures; 28 (iii) a relaxation related to the conduction losses and Maxwell-Wagner-Sillar (MWS, also known as the interfacial relaxation) [29][30][31][32][33][34][35][36][37][38] at high temperatures. The high temperature process overlaps with the 7, 1750033 (2017) conductive losses because of its nature; it occurs at the interface boundary between constituents in composites.…”
Section: Dielectric Relaxationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed previously, at high temperatures close to 300 C, the data for the wet and dried sample are converging to each other indicating the similarities in both responses and confirm that the initial measurement in the first ramp is a dry-bake cycle. The relaxations related to the molecular nature of the material are associated in the dried sample, which indicated three significant processes; (i) a low temperature relaxation attributed to the local (segmental) molecular motion often called as the Johari-Goldstein ( ) relaxation; [26][27][28] (ii) the glass-transition related loss from cooperative ( ) relaxation at mid-temperatures; 28 (iii) a relaxation related to the conduction losses and Maxwell-Wagner-Sillar (MWS, also known as the interfacial relaxation) [29][30][31][32][33][34][35][36][37][38] at high temperatures. The high temperature process overlaps with the 7, 1750033 (2017) conductive losses because of its nature; it occurs at the interface boundary between constituents in composites.…”
Section: Dielectric Relaxationsmentioning
confidence: 99%
“…37,38,[49][50][51] Here, we assume that the electrical properties of the studied composite system (labeled \c") could be represented with a binary mixture approach where two phases are the resin (labeled \r") and inorganic filler particles (labeled \f "). Once we adopt this approach, the electrical properties of the highly filled composite can be expressed with the scaled complex permittivity approach as follows: [50][51][52][53][54][55] ð…”
Section: Dielectric Mixture Approachmentioning
confidence: 99%
“…In such an approach, the signs of the calculated g in Fig. 2 are used as a pre-distribution for the sign of the polarization distribution in a numerical method based on the constrained least-squares algorithm [6,7,8]. The averaging of g values is performed by considering various bin sizes.…”
Section: Eq (3) Is Written As a Matrix Equationmentioning
confidence: 99%
“…(1). The method * Electronic address: enis.tuncer@physics.org has previously been applied to extract the distribution of relaxation times from dielectric spectroscopy data [6,7] and the spectral density function (distribution) of dielectric mixtures [8]. In those problems, the distributions were probability densities of relaxation times and spectral parameters.…”
mentioning
confidence: 99%
“…In particular, we recently showed that the ac electrical properties of Co nanoparticles embedded into a dielectric ZrO 2 matrix display a complex lowfrequency absorption phenomenon 11,12 in the dielectric regime below the percolation threshold for Co that mimics the so-called universal response 13 of disordered dielectric materials, which remains a topic of very active experimental and theoretical researches. [14][15][16][17] In particular, the ac conductivity and permittivity are characterized in disordered dielectric materials by the existence of a transition above a critical value of the angular frequency from a low-frequency dc plateau to a dispersive high-frequency region, where both the conductivity and the permittivity show an anomalous fractional power-law dependence on the angular frequency. 13,17 This dispersive behavior has been observed in a large variety of materials, 14 suggesting that the universal response is an intrinsic property associated with the geometry and actual characteristics of the conduction network rather than the specific mechanisms responsible for the conduction processes and the nature of the atoms constituting those materials.…”
Section: Introductionmentioning
confidence: 99%